Intangible Capital, Stock Markets and Investments: Implications for Macroeconomic Stability - Gerba, Eddie (Journal of Accounting and Finance, 2020)
I link investments in total working capital to a forward-looking endogenous stock market mechanism in an otherwise standard New Keynesian financial frictions model with rational agents. The effects on macroeconomic stability are substantial. Impulse responses to shocks are on average three times more volatile than in a standard financial accelerator framework. Likewise, the fit of the extended model to post-2000 US data is considerably improved. Optimal monetary policy that includes explicit and timely reaction to stock market developments is strictly preferred in this economy.